The first damselflies from the lowermost eocene of Denmark, with a description of a new subfamily (Odonata, Zygoptera: Dysagrionidae) - Rust, Jes (2008)
Eodysagrion mikkelseni gen. et sp. nov., type species of the new subfamily Eodysagrioninae, and the dysagrionine Primorilestes madseni sp. nov., the first thaumatoneurid damselflies from the lowermost Eocene of Denmark, are described. They confirm the presence of this American family in the Palaeogene of Western Europe